VMware vCenter cookbook : over 65 hands-on recipes to help you efficiently manage your vSphere environment with VMware vCenter /: over 65 hands-on recipes to help you efficiently manage your vSphere environment with VMware vCenter. (2015) - Kuminsky, Konstantin
No abstract available